A combined experimental and computational study of the effect of electron irradiation on the transport properties of aromatic and aliphatic molecular self-assemblies - Y. Tong (18394389) (2022)
Intermolecular cross-linking through electron irradiation is proven to be an effective tool to improve the mechanical and electronic properties of molecular self-assembled monolayers (SAMs), which is known to be a key player for material nanoarchitectonics. Here we study the effect of electron irradiation on the electronic transport properties of aromatic 5,5′-bis(mercaptomethyl)-2,2′-bipyridine (BPD; HS-CH2-(C5H3N)2-CH2-SH) and electron saturated 1-dodecanethiol (C12; CH3-(CH2)11-SH) molecules self-assembled on an Au (111) surface. We could not create any successful junctions for transport measurements for the electron irradiated C12 SAMs due the deterioration of such molecules with electron saturated nature. For the aromatic molecules, the electron bombardment results in significant reduction of the current despite the electron irradiation-induced intermolecular cross-linking, which should create extra transport channels for charge carriers. The current rectification also reduces after the electron bombardment. In order to interpret the experimental results and give right diagnostics behind the decrease of the current through the junction after electron irradiation, we supplement the experiment with quantum transport calculations using Green's functional formalism in combination with density functional theory. The simulation results show that the reduced current after electron irradiation can be related to the detachment of the molecules from the gold substrate and reattachment to other molecules. The formation of diamond-like structures due to intermolecular-cross linking can also be the reason for the reduced current obtained in the experiments. We have also considered the case when the BPD molecules get broken-conjugated due to the attachment of extra hydrogen atoms to the carbon backbone of the molecule. This structural modification also results in a significant decrease of the current. These findings can be useful in understanding the processes during the electron irradiation of molecular SAMs. Other Information Published in: Nanoscale Advances License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://doi.org/10.1039/d2na00040g